LEGAL PROTECTION OF WOMEN WORKERS ON THE NIGHT SHIFT ( COMPARISION OF INDONESIA AND MALAYSIA) - Okstriana, Nur Rifa; Munika, Agnes Silvia (Indonesian Journal of Labour Law and Industrial Relations, 2024)
Along with the development of the global economy and the current needs of the industry, many companies have implemented work systems for a period of approximately 24 hours. The working time is divided into three work shifts. Among the three shifts, the night shift (23.00 - 05.00) is the most risky for female workers, especially in meeting their economic needs, due to working hours that do not match the body's rhythm. However, many women choose to work night shifts because of the flexibility of the time offered. To address the challenges faced by female night shift workers, strong support from families and companies is needed. This study aims to compare legal protection for female workers on night shifts in Indonesia and Malaysia. The method used is a comparative analysis of labor regulations in both countries, including Law No. 13 of 2003 on Manpower in Indonesia and the Employment Act 1955 in Malaysia. The results show that while the two countries have similar regulations in terms of not requiring specific permits for female workers over 18 years of age and employers' obligations to provide health and safety facilities, Malaysia is stricter in oversight and more specific in discussing the limits on working hours and facilities that must be provided. In Indonesia, the implementation of regulations is still ineffective, so it is necessary to increase supervision and legal awareness. This study emphasizes the importance of effective legal protection to improve the welfare of women workers who work night shifts.